2014
DOI: 10.1016/j.dcn.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Averaging, not internal noise, limits the development of coherent motion processing

Abstract: HighlightsMotion processing abilities develop gradually through childhood.This lengthy development could be due to local noise and/or poor averaging.5–11-year-olds and adults performed equivalent noise and motion coherence tasks.Through childhood, internal noise reduces and averaging increases.Yet, only improved averaging explains developments in motion coherence sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 68 publications
3
50
1
Order By: Relevance
“…Our results for effective sample size are lower than the majority of studies reporting samples for averaging size33 and motion31, however Manning et al 34. have observed sampling efficiencies at or below one for motion in children.…”
Section: Discussioncontrasting
confidence: 84%
“…Our results for effective sample size are lower than the majority of studies reporting samples for averaging size33 and motion31, however Manning et al 34. have observed sampling efficiencies at or below one for motion in children.…”
Section: Discussioncontrasting
confidence: 84%
“…Given our results, this challenge constitutes a different degree of difficulty for both groups, as the ASD group clearly outperforms the TD group. A recent study by Manning et al [] found evidence for increased sampling or increased pooling of information in individuals with ASD relative to TD individuals, when participants were presented with sets of moving dots. Translating this idea of increased sampling to our findings entails that, compared with TD participants, participants with ASD would use (or sample across) more items in order to properly encode an ensemble.…”
Section: Discussionmentioning
confidence: 99%
“…Many object and scene features have been investigated in relation to ensemble processing. Low‐level features that have been investigated include size [e.g., Ariely, ; Chong & Treisman, ], number [e.g., Halberda, Sires, & Feigenson, ], orientation (e.g., Dakin, Bex, Cass, & Watt, ; Dakin & Watt, ], and motion direction [e.g., Manning, Dakin, Tibber, & Pellicano, ]. High‐level visual features that have been evaluated include facial emotions [Haberman & Whitney, ] and spatial layout [Alvarez & Oliva, ].…”
Section: Introductionmentioning
confidence: 99%
“…Most CM studies use random dot kinematograms (RDKs), for which participants are required to discriminate the overall dominant motion direction of a field of dots, while a certain percentage of the dots moves randomly across the display. However, rather than being a direct test for global processing capacities, as frequently thought, CM tasks actually confound the capacity to integrate local inputs into global percepts with one's sensitivity to noise (Dakin, Mareschal, & Bex, 2005;Manning, Dakin, Tibber, & Pellicano, 2014). While RDK performance in ASD is predominantly interpreted in relation to possible global integration deficits (or weak central coherence), the results could also be interpreted in terms of the participants' ability to cope with noise inherently present in the displays.…”
Section: Robustness In Perception and Actionmentioning
confidence: 99%